Ideologia e comunicação midiática quanto à violência sexual contra mulheres: contribuições à compreensão da cultura do estupro - Wurdig, Karolina Kuhn (2019)
The rape culture has its manifestation consolidated when there are women being blamed in cases of sexual violence. This dissertation had as objective to analyze how online media constructs meanings about the sexual violence against women, identifying possible ideological strategies used which could be reinforcing the rape culture. Furthermore, we were interested in identifying how the victims and the aggressors are described in online media, as well as to observe if the intersectionalities (between gender, class, and race) are considered in the articles. The research is part of the integrated project called “Precarious Lives in the cyberworld” – Studies about violence, power and intersectionality in the hierarchical systems. We start from the perspective of the Critical Social Psychology and of a theoretical construction sustained in the operational methods of the ideology proposed by the sociologist John B. Thompson. The Theory of Social Representations, the Gender Studies and the Feminist Theories also contributed to the analyses. We worked with 99 newspaper reports involving rapes of adult women, starting from a quali-quantitative approach. The quantitative approach contributed for a broader view of the available data in the news reports and the relationships stablished with the discourses. Quantitatively, we employed the methodology of the Depth Hermeneutics proposed by Thompson and the Critical Discourse Analysis proposed by Van Dijk. Thereafter, some results from the analyses helped us to think about women being blamed for being in a position of sexual violence such as, for example, in the news reports that referred to places and circumstances of the situation where happened the violence. We perceived that these specifications contributed with the idea of co-accountability of women and the creation of the ideal victim stereotype. The data that involved the analysis of men, perpetrators of the sexual violence, enabled us to recognize the class aspect as a way of reporting differently the cases. The aggressors who were part of symbolic elites had their cases put in context in distinctive ways, providing a larger space for defense, specifying their personal lives and careers. We concluded that the way the analyzed news reports about rape are presented end up strengthening the rape culture, as they present expressions that emphasize the participation of the victims over the action of the aggressors. The ideological strategies attached in the news reports involving the victims and the aggressors, made it possible to recognize activities yet in the sense of maintaining the dominant ideology, corroborating with the maintenance of relations of domination through structures of gender and class.